Evaluation of Validity and Efficiency of Diagnostic Criteria in Autoimmune Hepatitis in Children - Mohammadhadi Imanieh; Nazanin Amin Farzaneh; Seyed Mohsen Dehghani; Maryam Gholami Shahrebabak; Samaneh Hamzelou Hosseinabadi (Turkish Journal of Gastroenterology, 2021)
Background: Autoimmune hepatitis (AIH) is a progressive inflammatory liver disease with various clinical symptoms, but treatment and prevention of hepatic failure and cirrhosis is possible with early diagnosis. However, no specific test has been approved for the diagnosis of AIH. In 2008, the International Autoimmune Hepatitis Group (IAIHG) developed a simplified diagnostic scoring system that has been widely used in practice. Nevertheless, it cannot distinguish AIH from Primary Sclerosing Cholangitis (PSC) and consensus is lacking with respect to its validity, sensitivity, and applicability for children patients. The newer 2018 version also requires validation. The present study intends to evaluate the validity and efficiency of the IAIHG simplified scoring system and new scoring system in children with AIH. Methods: The present study is a non-interventional case–control study covering 152 patients with hepatic diseases (83 patients with AIH and 69 patients with Wilson disease (WD)). Titers of autoantibodies, IgG levels, hepatic histology, and absence of viral hepatitis were scored and calculated according to IAIHG diagnostic criteria. Statistics software package (SPSS) and draft receiver operating characteristic (ROC) curves was used to analyze data and determine value of diagnostic criteria. Result: In our study, both scoring systems’ accuracy was good in AIH diagnosis, although new score displays higher sensitivity and specificity, suggestive of greater accuracy and predictive strength. Conclusion: Our study is the first validation study of the new scoring system in diagnosing AIH, and further studies require verifying this scoring system. Cite this article as: Imanieh M, Farzaneh NA, Dehghani SM, Gholami Shahrebabak M, Hosseinabadi SH. Evaluation of validity and efficiency of diagnostic criteria in autoimmune hepatitis in children. Turk J Gastroenterol. 2021; 32(6): 526-531.